PENGARUH PENERAPAN QUANTUM LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMA NEGERI 4 SURAKARTA TAHUN PELAJARAN 2011/2012 - Faisal Imam Prasetyo; Slamet Santosa; Puguh Karyanto (Universitas Sebelas Maret, 2012)
ABSTRAK The purpose of this research is to ascertain the influence of Quantum Learning toward biology learning achievement of 10th grade students at SMA Negeri 4 Surakarta in academic year 2011/2012. The research was quasi experiment research using quantitative approach. The research was designed using posttest only control design. Experimental group applied Quantum Learning. Control group applied discussion, classical course and question-answer method. The populations of this research were all of 10th degree students at SMA Negeri 4 Surakarta in academic year 2011/2012. The samples of this research were the students of 10thK as experiment group and 10thJ as control group. The sample of this research was established by cluster random sampling. The data was collected using questionnaire, multiple choice test, observation form, and document. The hypotheses analyzed by t-test. The research concluded that application of Quantum Learning had significant effect toward biology learning achievement in cognitive, affective, and psychomotor of 10th grade students at SMA Negeri 4 Surakarta in academic year 2011/2012. Kata kunci: Quantum Learning, Biology Learning Achievement